Strengthening the Creative Economy through Branding and E-Commerce Training - Muhamad Rizki; Riani Rachmawati; Mitra Trima Dessincer Putri; Umi Rusilowati; Chua Toh Hua; Richard Andre Sunarjo (ADI Publisher, 2026)
This community service activity is motivated by the low level of understanding among creative economy actors in developing product branding and utilizing e-commerce as a digital marketing medium, which has resulted in limited business competitiveness amid the development of the digital market. Based on this condition, the program aims to analyze the contribution of branding and e-commerce training in improving the capacity of creative economy actors as well as the effectiveness of digital product promotion. The activity was conducted using a descriptive qualitative method with data collection techniques consisting of observation, interviews, and documentation, along with pre- and post-training evaluations to identify changes in participants’ knowledge and skills. The results of the community service involving 42 participants indicated an improvement in participants' ability to build brand identity, enhance product appearance and presentation, and manage marketing through e-commerce platforms in a more structured and effective manner, accompanied by increased confidence in promoting products and expanding market reach. The discussion confirms that the integration of branding and e-commerce training is an effective strategy in strengthening the creative economy as it improves competitiveness, digital readiness, and the sustainability of creative business actors. Therefore, branding- and e-commerce-based training programs need to be developed continuously through collaboration among academics, government, and industry practitioners to support adaptive and sustainable creative economic growth.